2000
DOI: 10.1136/gut.46.3.350
|View full text |Cite
|
Sign up to set email alerts
|

Human intestinal epithelial cells secrete interleukin-1 receptor antagonist and interleukin-8 but not interleukin-1 or interleukin-6

Abstract: Conclusions-IECs from normal mucosa express and secrete IL-1ra and low amounts of IL-8, but no IL-1 or IL-6. In inflamed mucosa the secretion of IL-1ra by IECs is slightly increased but may be not suYcient to antagonise the greatly increased production of proinflammatory cytokines by LPMNCs and the IECs themselves. (Gut 2000;46:350-358)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
55
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 31 publications
9
55
0
Order By: Relevance
“…However, these studies did not explore the functional consequences of TLR2 signaling in IEC. Our findings demonstrate that IEC are poorly responsive to a variety of TLR2 ligands with respect to proinflammatory gene expression and IL-8 secretion, two outcomes relevant to acute and chronic intestinal inflammation (92)(93)(94). Although the response to certain TLR2 ligands could be restored by transgenic expression of TLR2 and TLR6, IEC remained poorly responsive to bacterial lipopeptide suggesting that, in addition to TLR2 and TLR1, other coreceptors or signaling molecules may be functionally deficient as well.…”
Section: Discussionmentioning
confidence: 75%
“…However, these studies did not explore the functional consequences of TLR2 signaling in IEC. Our findings demonstrate that IEC are poorly responsive to a variety of TLR2 ligands with respect to proinflammatory gene expression and IL-8 secretion, two outcomes relevant to acute and chronic intestinal inflammation (92)(93)(94). Although the response to certain TLR2 ligands could be restored by transgenic expression of TLR2 and TLR6, IEC remained poorly responsive to bacterial lipopeptide suggesting that, in addition to TLR2 and TLR1, other coreceptors or signaling molecules may be functionally deficient as well.…”
Section: Discussionmentioning
confidence: 75%
“…IL-1Ra specifically inhibits IL-1 activities by binding to IL-1 receptors, but does not display agonist activity [5,12,16,[19][20][21][22]. In the intestinal mucosa, epithelial cells and lamina propria mononuclear cells are the major sources of IL-1Ra [23]. An imbalance between the production of IL-1 and IL-1Ra has been described in freshly isolated intestinal mucosal cells [24] and in colonic mucosal biopsies obtained from inflamed intestinal tissue of IBD patients [25].…”
Section: Introductionmentioning
confidence: 99%
“…Periephitelial region of the small bowel and subephitelial dome of the Peyer's plaques are some of the places that they are located. In these localizations, the first defense mechanism is formed against the pathogens found in the colon lumen [16,17]. In CC cases, considering the immune response system's systematic response in which cellular unit plays a leading role, presence of inflammatory cells found somewhere (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In CC cases, considering the immune response system's systematic response in which cellular unit plays a leading role, presence of inflammatory cells found somewhere (e.g. gastric and/or duodenal mucosa) other than the location where the disease is primarily localized must be checked out and their presence in such locations will support the diagnosis of the disease [16,17]. Recently, it has been reported that MMA found in gastroduodenal mucosa by immunochemical methods supports the diagnosis of CD.…”
Section: Discussionmentioning
confidence: 99%